Implementasi Google Maps API Pemetaan Jalur Evakuasi Bencana Alam di Kabupatem Lombok Utara - Khaerul Yasin; Ahmat Adil (Universitas Bumigora, 2019)
Basically, Indonesia is traversed by three active tectonic plates namely the Indo-Australian Plate in the south, and the Eurasian Plate in the north and the Pacific Plate in the east. The plates collide with each other because the Indo-Australian Plate movement drops below the Eurasian plate. As a result of this accumulation, it caused earthquakes, volcanoes, and faults or faults in parts of Indonesia. In the Geographic Information System evacuation routes will be used by Google maps Api to implement the spatial map making of evacuation routes. Google Map Api is an application interface that can be accessed via javascript so that Google Map can be displayed on the web page that we are building. The result or output to be achieved is the creation of a geographic information system mapping natural disaster evacuation route in the North Lombok district that can be run on a Web platform. Based on the trials conducted it can be concluded that this application can help the community to find the location of evacuation routes and gathering points in accordance with the districts and villages where they live.